The role of extracorporeal membrane oxygenation in an acute basal ventricular septal rupture. (29th August 2019) - Matos, Daniel; Madeira, Marcio; Nolasco, Tiago; Neves, José Pedro
Abstract: A 74-year-old man was admitted with a post-acute myocardial infarction basal ventricular septal rupture. Onset of cardiogenic shock led to the implantation of a percutaneous veno-arterial extracorporeal membrane oxygenation (ECMO) system with an additional venous drainage cannula into the right ventricle. The ventricular septal defect was repaired with concomitant tricuspid valvuloplasty and mitral bioprosthesis implantation after 14 days. ECMO support was temporarily converted into a veno-venous system to wean the patient off cardiopulmonary bypass. The patient was discharged 3 weeks after surgery. This case illustrates the role of this extracorporeal life support system in the setting of postinfarction ventricular septal rupture.